Enhanced bath immersion vaccination through microbubble treatment in the cyprinid loach. Issue 91 (August 2019) - Yun, Saekil; Giri, Sib Sankar; Kim, Hyoun Joong; Kim, Sang Geun; Kim, Sang Wha; Kang, Jung Woo; Han, Se Jin; Kwon, Jun; Oh, Woo Taek; Chi, Cheng; Jun, Jin Woo; Chang Park, Se
Abstract: Immunization by bath immersion is likely the simplest method of fish vaccination. Although the route of immunogenicity has not been fully identified, immersion vaccination is clearly a useful labor-saving technique. In this study, microbubble (MB) treatment was assessed for its ability to improve the efficacy of bath immersion vaccination in the cyprinid loach. MBs are commonly defined as minute particles of gas with a diameter of less than 100 μm, which generated free radicals. Here, the efficacy of MB treatment for vaccination enhancement in the cyprinid loach was assessed in direct challenge experiments using the virulent Aeromonas hydrophila JUNAH strain; assessments comprised agglutination titer assay and non-specific parameter analysis. Agglutination titers were high in loaches that were immunized via injection with inactivated cells (FKC group); however, non-specific immune activation parameters (e.g., lysozyme, superoxide dismutase, and phagocytic activity) were more increased in loaches that were immunized via bath immersion with MB treatment. Moreover, MB-treated loaches showed comparable survival rates, relative to loaches immunized via injection with formalin inactivated cells. Thus, higher levels of non-specific immune parameters suggest increased efficacy of this vaccine approach. Improving the effectiveness of bath immersion vaccine will increase its affordability and ease of application in aquaculture. Highlights: Microbubble treatment was used for bath immersion vaccination in the cyprinid loach. Non-specific immune activation parameters were increased by microbubble treatment. Bath immersion with microbubble treatment was comparable to original injection vaccine in survival rates. This approach may increase vaccine efficacy, improving its use in aquaculture.